Psychological Factors in Oral Lichen Planus - Abhishek Ranjan Pati1, Rajat Panigrahi1, Smita R. Priyadarshini1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
It has been known for centuries that mental/emotional factors are correlated to numerous physical diseases.Traditionally we regard mind (psyche) and body (soma) separate but where and how do they interact?The very idea of psychological medicines was told by Sigmund Freud, who used conversion hysteria inexplaining the effects of emotional disparity turned into bodily or somatic symptoms